Is Multicore Hardware for General-Purpose Parallel Processing Broken? - Vishkin, Uzi (Communications of the ACM, 2014)
The article presents the author's views on some shortcomings of parallel computing and the prospects for future. According to the author, the ideal impact would drive the field toward seeking possibility of systemic advancement. The author also states that many more application domains could benefit significantly from exploiting irregular parallelism for speedups.